2017
DOI: 10.1007/s10862-017-9612-z
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Conduct Problems: Predictions from Daring Temperament and Risk Taking Behavior

Abstract: Objective Given its considerable public health significance, identifying predictors of early expressions of conduct problems is a priority. We examined the predictive validity of daring, a key dimension of temperament, and the Balloon Analog Risk Task (BART), a laboratory-based measure of risk taking behavior, with respect to two-year change in parent, teacher-, and youth self-reported oppositional defiant disorder (ODD), conduct disorder (CD), and antisocial behavior. Method At baseline, 150 ethnically dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…In particular, there is an association between behavioural intensity and thrill seeking, on the one side, and the likelihood of having more conduct problems, on the other. These results are in line with findings in children and adolescents [ 33 , 34 ] and suggest that the link between sensation seeking and aggressive, quarrelsome behaviour and short-temperedness is already apparent in young childhood. In line with our hypothesis, we also found that children who present more thrill seeking showed more signs of hyperactivity/inattention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, there is an association between behavioural intensity and thrill seeking, on the one side, and the likelihood of having more conduct problems, on the other. These results are in line with findings in children and adolescents [ 33 , 34 ] and suggest that the link between sensation seeking and aggressive, quarrelsome behaviour and short-temperedness is already apparent in young childhood. In line with our hypothesis, we also found that children who present more thrill seeking showed more signs of hyperactivity/inattention.…”
Section: Discussionsupporting
confidence: 91%
“…To date, very few studies have examined this relationship. Previous findings suggest an association between sensation seeking and externalising behavioural difficulties, namely conduct problems [ 33 , 34 ] in children and adolescents, and hyperactivity symptoms in adults [ 35 ]. In respect to internalising problems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study, to our knowledge, to examine whether the interaction between genetic loading for CD and community disadvantage is associated with sexual health outcomes among urban women. Past work has indicated that behavioral reports of conduct problems and community disadvantage are individually predictive of sexual risk taking [9,20]. Results from the present study extend previous findings by highlighting the combined effects of genetic propensity for CD and disadvantage on sexual risk behaviors among women.…”
Section: Discussionsupporting
confidence: 82%
“…Conduct disorder (CD) is defined as a syndrome characterized by a pattern of antisocial behaviors that often infringes on the rights of others and violates social norms [9,10]. CD has been consistently associated with sexual health outcomes among women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation